The clinical characteristics and surgical strategy in infants with lingual thyroglossal duct cyst - Fenghua Qin; Yihua Ni; Wenxia Chen (Brazilian Journal of Otorhinolaryngology)
Objectives: Lingual Thyroglossal Duct Cysts (LTDCs) are a rare variant of thyroglossal duct Cyst (LDC). This study aimed to explore the efficacy of transoral excision of LTDC and evaluate the added benefit of concomitant management of laryngomalacia during the surgical intervention. Methods: Infants with LTDCs were retrospectively collected from our department from January 2009 to January 2022. The baseline characteristics, clinical symptoms, the features of transnasal flexible fiberoptic laryngoscopy, CT and MRI, surgical treatments, and follow-up results were described and analyzed. Results: 50 babies with LTDCs were included. Five infants had urgent bedside cyst aspiration prior to surgery for respiratory distress. All patients underwent cyst resection. Concurrent LTDC and laryngomalacia were found in 10 patients on preoperative laryngoscopy. Due to breathing and swallowing issues, these infants underwent transoral cyst removal and supraglottoplasty in the same surgical setting. 3 large cyst cases, laryngomalacia were undetectable pre-cystectomy. When extubation failed after 1weeks, repeat laryngoscopy revealed severe laryngomalacia necessitating successful supraglottoplasty. All patients were discharged from the hospital once oral intake is safe and adequate. Conclusion: Transoral surgery for LTDC is an effective and safe surgical treatment. Additionally, identifying and promptly addressing other laryngeal conditions, such as laryngomalacia, significantly enhances the success rate of the surgery. Level of evidence: 4.